NEOLIBERALISM AND SOCIAL WORK REGULATION: Implications for Epistemic Resistance - Heron, Barbara (Canadian Social Work Review / Revue canadienne de service social, 2019)
The question of how through social work practice, theory and research social workers engage in “epistemic disobedience” in respect to the “epistemicide” of Others’ knowledges is crucial in the current neolielberal context. However, the possibilities of such resistance are becoming increasingly constrained by the encroachment of licensing requirements for social work professionals. This paper considers how the turn to professional regulation in social work via licensing competency standards further entrenches Western ways of knowing, while at the same time working in concert with neoliberalism to transform the social work profession in ways that stand to remove it from the reach of epistemic disobedience. The Canadian Council of Social Work Regulators’ competency standards are taken as the starting point for an analysis, which seeks to articulate the intersecting impacts of neoliberalism in social work practice, and the crucial place of social work regulation within this web of effects. In conclusion, the implications for social work education are raised and the urgency of epistemic resistance is considered.